Power magnetic devices a multi-objective design approach - Sudhoff, Scott D. (Wiley IEEE Press, 2014)
Presents a multi-objective design approach to the many power magnetic devices. This title addresses the design of power magnetic devices - including inductors, transformers, electromagnets, and rotating electric machinery - using a structured design approach based on formal single- and multi-objective optimization.